Measuring the Speed of Docking Ship with Total Station - Andrzej Felski (Communications - Scientific letters of the University of Zilina, 2022)
The big modern ships are the largest mobile objects that exist in nowadays world. Their huge mass and length in combination with their limited maneuverability can result in the risk of extreme destructions of the infrastructure, as well as environment, in the case of even minor malfunction of any of its elements. The main danger is the kinetic energy of such a colossus and in these circumstances the accuracy of information on the ship's speed becomes particularly important. This is the reason of a growing interest in various systems designed to support harbor pilots during the maneuvers. The most popular ones are based on laser-measurement of the distance, as the rule, installed as static installation in the quay. This article presents the results of the experiments of vessel’s speed measurements when approaching the quay with use the geodetic total stations in a reflectorless variant.